Book Reviews (Journal of Finance, 1981)
Book reviewed in this article: Cases on Financial Institutions . By DIXON C. CUNNINGHAM, CHARLES O. MEIBURG and MICHAEL C. WALKER Portfolio Theory, 25 Years After . Edited by E. J. ELTON and M. J. GRUBER A Treatise on Markets, Spot, Futures, and Options . By JOSEPH M. BURNS Stabilization of International Commodity Markets . By PAUL HALLWOOD International Lending, Risk & the Euromarkets . By ANTHONY ANGELINI, MAXIMO ENG and FRANCIS A. LEES College Financial Management . By E. EUGENE CARTER Fundamentals of Finance . By RICHARD A. STEVENSON New Sources of Capital for the Savings and Loan Industry: Proceedings of the Fifth Annual Conference.